Provision of housing and quality of life : the Geographic study of Extension 44 in the Polokwane Municipality - Ngoatle, Thabang (My University, 2021)
The study focuses on Extension 44 in the Polokwane, an exclusively Black urban Township defined as a liveable geographical space consisting of both activity and awareness space (perpetual) space. Central to this research is its origins and existence as part of the urban racial spatial organization of Polokwane Municipality, viewed in terms of the Colonial, Apartheid and the traditional theoretical models depicting the internal structure of urban centres, including how it fits into the post-Apartheid urban planning policies, the provision of housing (types and quality), including the availability of physical and social infrastructure, how the residents perceive and evaluate these in relation to the residents’ quality of life in that area. The questions raised are (i) when and why was Extension 44 in the Polokwane municipality established? (ii) Who provides what type and quality of housing in the township? (iii) And lastly what perceptions do the residents have regarding housing and living conditions in Extension 44? Therefore, the study draws its significance as falling under both Settlement (Urban) and Behavioural geography. The former deals with origins and the nature of habitable space (settlements) while the latter is concerned, among others, with how people perceive their habitat.
Thesis (M.Sc. (Geographic Studies)) -- University of Limpopo, 2021
Keywords: Provision of housing; Quality life; Extension 44; Polokwane Municipality; Housing policy -- South Africa -- History; Public housing -- South Africa; Land use, urban -- South Africa